CASE REPORT ON A POSTNATAL MOTHER WITH PERINEAL WOUND PAIN AND LACTATION DISORDERS IN THE WORKING AREA OF THE AROSBAYA COMMUNITY HEALTH CENTER, BANGKALAN REGENCY - Nadia Fardiana Isnaini Lestari; Deasy Irawati; Siti Anisak; Sri Wayanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The postpartum period is a crucial recovery phase for mothers, often complicated by perineal pain due to tears or episiotomy. This pain can restrict movement, hinder daily activities, and disrupt lactation patterns. This case report describes midwifery care for a postpartum mother with grade II perineal lacerations and lactation issues. Data were collected through interviews, observations, documentation, and physical examinations. Pain was assessed using the Numeric Rating Scale (NRS) and Visual Analog Scale (VAS), while lactation patterns were evaluated based on frequency, duration, and breastfeeding techniques. The subject was a P1A0 mother on the third day postpartum. Interventions included personal hygiene education, nutrition, sitting position, early mobilization, warm compresses, lavender aromatherapy, and support for optimal lactation. Results showed that during the first visit, the mother experienced moderate to severe pain and limited mobility. However, after three visits, pain intensity decreased significantly, mobility improved, and the mother’s self-care knowledge enhanced. Lactation patterns were smooth, wounds healed without infection, and uterine involution was normal. Daily activities resumed without hindrance. This midwifery care effectively reduced perineal pain, improved lactation, and enhanced the mother’s self-care understanding. Support through education, family involvement, and safe, non-pharmacological interventions helped the mother navigate postpartum recovery without complications.